Study of Ultrasonic Wave Velocity in the Binary Mixture Liquids of Carbon Tetra Chloride and Propyl Ethyl Ketone (CCl4+PEK)] At the Temperature 308.15K (Bulletin of Pure and Applied Sciences – Physics, 2020)
In the present paper, we have measured and investigated the ultrasonic velocity (U),  density ( ), viscosity ( ), adiabatic compressibility ( a ), intermolecular free length  (Lf), molecular volume (Vm), available volume (Va), free volume (Vf), specific acoustic  impedance (Z), Gibb’s free energy (G) in binary liquid mixtures of carbon tetra  chloride and propyl ethyl Ketone (CCl4+PEK)] at 308.15K.